A Machine Learning Approach to the Automatic Evaluation of Machine Translation - Corston-Oliver, Simon; Gamon, Michael; Brockett, Chris (Association for Computational Linguistics, 2001)
We present a machine learning approach to evaluating the well-formedness of output of a machine translation system, using classifiers that learn to distinguish human reference translations from machine translations. This approach can be used to evaluate an MT system, tracking improvements over time; to aid in the kind of failure analysis that can help guide system development; and to select among alternative output strings. The method presented is fully automated and independent of source language, target language and domain.